Consumers’ Willingness to Pay for Alternative Fueled Rental Cars : A Choice Experiment Study in Luleå, Sweden - Björklund, Emma (Luleå tekniska universitet, Institutionen för ekonomi, teknik och samhälle, 2018)
Sweden, as a country, has set the goal to achieve a fossil independent vehicle fleet by 2030, which means that Sweden has to reduce its CO2 emissions by 80 percent. Sources argue that the regulations and different implementations that have been done are not enough to reach the 80 percent reduction in time. The purpose of this paper is to analyze consumers’ preferences towards alternative fuel vehicles by estimating the willingness to pay for rental cars in Sweden. The paper also tries to define the explanatory factors for choosing an alternative fuel vehicle. The data used in this thesis was collected through a choice experiment questionnaire that was distributed to employees and students at Luleå University of Technology. The study concludes that respondents have a willingness to pay at approximately SEK 280 extra to rent and use an electric rental car.